2003
DOI: 10.1021/bi035339n
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maturase Binding and Mg2+ Concentration on Group II Intron RNA Folding Investigated by UV Cross-Linking

Abstract: The Lactococcus lactis Ll.LtrB group II intron encodes a reverse transcriptase/maturase (LtrA protein) that promotes RNA splicing by stabilizing the catalytically active RNA structure. Here, we mapped 17 UV cross-links induced in both wild-type Ll.LtrB RNA and Ll.LtrB-Delta2486 RNA, which has a branch-point deletion that prevents splicing, and we used these cross-links to follow tertiary structure formation under different conditions in the presence or absence of the LtrA protein. Twelve of the cross-links are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 43 publications
6
61
0
Order By: Relevance
“…These differences suggest that the active structures of aI5␥ and bI1 at physiological KCl and Mg 2ϩ concentrations may differ in significant ways from those formed under self-splicing conditions. A similar conclusion was reached for the maturase-promoted and selfsplicing reactions of the Ll.LtrB intron based on chemical structure mapping and analysis of UV-induced RNA-RNA cross-links (7,8). We suggested previously that inactive structures stabilized by high Mg 2ϩ concentrations might contribute to the strongly decreased rate of self-splicing compared with maturase-dependent splicing of that intron (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These differences suggest that the active structures of aI5␥ and bI1 at physiological KCl and Mg 2ϩ concentrations may differ in significant ways from those formed under self-splicing conditions. A similar conclusion was reached for the maturase-promoted and selfsplicing reactions of the Ll.LtrB intron based on chemical structure mapping and analysis of UV-induced RNA-RNA cross-links (7,8). We suggested previously that inactive structures stabilized by high Mg 2ϩ concentrations might contribute to the strongly decreased rate of self-splicing compared with maturase-dependent splicing of that intron (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, a protein-dependent in vitro splicing system has been developed only for the RT͞maturase protein encoded by the mobile Lactococcus lactis Ll.LtrB intron (5, 6). Studies using this system showed that the maturase binds specifically to the intron RNA and promotes its splicing by stabilizing the catalytically active RNA structure (7,8).In addition to proteins that stabilize specific RNA structures, cellular RNAs may require RNA chaperones to disrupt stable inactive structure (''kinetic traps'') during RNA folding (9, 10). In the case of group I and II introns, this RNA chaperone function is thought to be fulfilled by specific DExH͞D-box proteins (11, 12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The splicing of the group II intron aI2 depends on the intron-encoded p62 maturase, which by analogy to the Lactobacillus lactis Ll.LtrBencoded maturase (23,24) likely functions by stabilizing the catalytically active structure of the intron RNA. We were intrigued by the finding that expression of one copy of CYT-19 in mss116⌬ grown at 30°C restores wild-type levels of p62 (Fig.…”
Section: Mss116p Functions In Splicing Ai2mentioning
confidence: 99%
“…Protein concentrations were determined by Bradford assay (21), using LtrA protein whose concentration had been determined by using A 280 as a standard. The protein preparations were >98% pure, as judged by Coomassie blue-stained SDS-polyacrylamide gels Ll.LtrB lariat RNA was generated by self-splicing of a 971-nt Ll.LtrB RNA (902-nt Ll.LtrB intron flanked by 5'-and 3'-exon sequences of 32 and 37 nt, respectively) transcribed from BamHI-linearized pJNΔORF with phage T7 RNA polymerase, using a MEGAScript kit (Ambion, Austin, TX) (22). Self-splicing was carried out with 2 μM Ll.LtrB RNA in 1 ml of 0.5 M NH 4 Cl, 50 mM MgCl 2 , 40 mM Tris-HCl, pH 7.5 at 30°C.…”
Section: Reconstitution Of Rnpsmentioning
confidence: 99%